Knowledge, attitudes, and practices related to adult vaccination among adults and healthcare professionals across Mexico - Erika Hurtado-Salgado; Eduardo Lazcano-Ponce; Martín Romero-Martínez; Efrain Alonso Terrazas-Medina; Salma Pacheco; Adriana Guzman-Holst (PLoS ONE, 2026)
Background Despite substantial evidence supporting the benefits of vaccination across all age groups, achieving high vaccine coverage in adults remains a global challenge. Limited disease knowledge and vaccine hesitancy contribute to this issue. To increase vaccination rates, we need to understand the gaps in knowledge, attitudes, and practices (KAP) among adults and healthcare professionals (HCPs). Our primary objectives were to describe the KAP regarding vaccine-preventable diseases and vaccination among adults and HCPs in Mexico, and to identify differences by sociodemographic factors. Methods We conducted an observational cross-sectional survey study in three states in Mexico from July to October 2024. Two surveys were administered to adults aged ≥20 years and HCPs to capture outcomes of general vaccine and disease KAP, particularly for vaccine-preventable diseases such as herpes zoster (HZ), influenza, whooping cough, and respiratory syncytial virus (RSV). Results A total of 1,169 adults from the general population and 228 HCPs were included. Among the population group, 95.6% acknowledged the importance of vaccines, and 87.6% knew adults could receive routine vaccines. Knowledge of vaccine-preventable diseases ranged from high for influenza (97.3%) to limited for RSV (16.1%) and HZ (39.4%). Fewer knew about RSV (10.1%) and HZ (18.6%) vaccines. Only 23.5% of HCPs had recommended the HZ vaccine to older adults, while more did so for whooping cough (52.2%), influenza (96%). The main factors for HCPs to accept and recommend vaccinations were knowledge of the disease, complications, and vaccine efficacy and effectiveness. Also, 69.8% indicated that information about the disease was the most critical factor in vaccination recommendations. Conclusion The findings underscore the need to strengthen health communication and education, and address barriers that impede access to vaccination, particularly for less well-known vaccines. Bridging the gaps between KAP is essential to improving adult vaccination coverage, thereby reducing vaccine-preventable diseases and enhancing public health.